Internal structure of the cerebral hemispheres: an introduction of fiber dissection technique Estrutura interna dos hemisférios cerebrais: introdução à técnica de dissecação de fibras - Igor de Castro; Daniel de Holanda Christoph; Daniel Paes dos Santos; José Alberto Landeiro (Arquivos de Neuro-Psiquiatria)
The aim of this study is to introduce the fiber dissection technique and its importance in the comprehension of the three-dimensional intrinsic anatomy of the brain. A total of twenty brain hemispheres were dissected. Using Kingler's technique we demonstrated the intrinsic structures of the brain. The supra lateral aspect of the brain as well as the medial aspect were presented. The most important fiber systems were demonstrated. The use and comprehension of new neuroimaging techniques demand a better understanding of this fascinating anatomy. The knowledge acquired with this technique will improve our understanding of critical pathways of the central nervous system. O objetivo é mostrar a técnica de dissecação de fibras e sua importância na compreensão da anatomia tridimensional do cérebro. Um total de 20 hemisférios cerebrais foram dissecados. Usando a técnica de dissecação descrita por Kingler, pudemos demonstrar as estruturas que compõem a anatomia interna do cérebro. A anatomia da face súpero-lateral assim como da face medial foi apresentada. O uso e compreensão de novas técnicas de neuroimagem requerem um melhor conhecimento desta anatomia. O conhecimento adquirido com essa técnica contribuirá para o melhor entendimento de vias essenciais do sistema nervoso central.